Effectiveness of constant load exercise test on critical power output estimation in sedentary male subjects - Serhatlioglu, I.; Algul, S.; Yilmaz, B.; Ozcelik, O. (Wiley-Blackwell, 2014)
[Abstract Not Available]
Keywords: Anaerobic Threshold; Respiratory Compensation point; Critical power; Respiratory Gas Exchange